Screening for nasal carriage Staphylococcus aureus and their antibiotic susceptibility pattern among the health care workers in a tertiary care hospital, Nepal - Jha, Beena; Sapkota, J; Sharma, M; Mishra, B; Bhatt, CP (Journal of Kathmandu Medical College, 2018)
Background: The presence of Staphylococcus aureus in anterior nares of health care workers may serve as a major source of infection in hospital environment and act as a reservoir for the spread of Methicillin Resistant S. aureus between patients.Objective: The present study was conducted to determine the frequency of nasal carriage of S. aureus among the health care workers of Kathmandu Medical College Teaching Hospital and to assess the antibioticsusceptibility patterns of the Methicillin Resistant S. aureus isolates.Methodology: A total of 200 health care workers involved in the management of patients from the intensive care unit, Operation Theatre, postoperative wards, different wards and emergency department were screened for S. aureus by collecting their nasal swabs.Results: Out of 200 health care workers, only 10(5%) were S. aureus nasal carriers. Out of 10 S. aureus strains isolated six (60%) were methicillin sensitive S. aureuswhereas four (40%) were methicillin resistant S. aureus. The isolates were 100% sensitive to Linezolid, Vancomycin and Amikacin but showed highest resistant to Azithromycin (100%), followed by Cefixime (60%).Conclusion: This study concluded that 5% of health care workers were S. aureus carriers and proportion of Methicillin Resistant S. aureus and Methicillin sensitive S. aureus was 60% and 40% respectively.Journal of Kathmandu Medical CollegeVol. 7, No. 2, Issue 24, Apr.-Jun., 2018, page: 64-67